FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEMANDIRIAN PENDERITA/KELUARGA TB PARU - Gustina, Mely (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
Bengkulu city ranks fourth at 7,5%,the rate of TB(BTA+)first highs in publichealth service Sukamerindu,the second highest public health service Basuki Rachmad 25and hig hs into three PHC cage 19 people(Bengkulu City Health Office,2015),Beyond theinfluence of health against diseases such as pulmonary TB slum housing,moist facilitateTB bacteria to live and breed Government can facilitate and and development theoriessuch as Enabling,Empourment and Protecting. The autonomyof a society or group can bebased on the Ministry of Health 279/Menkes/SK/IV/2006. This study aimed correlationfactors that affect the level of independence with pulmonary tuberculosis?. Type of surveyresearch with cross sectional approach,the sample amounted to 31 obtained by purposivesampling technique,using univariate and bivariate analysis using Chay Square. Results ofstudy largely beyond health factors. Most of the level of independence of thepatient/family, there is a correlation factor protecting the activities of governmentfacilitation to the level of independence of the patient/family. Recomemended for patientswith medication adherence and trust health workers to patients/family as PMO when donewith a high awareness of the patient and family, it can accelerate healing.